Hydrophilic and hydrophobic TiO2 coatings by pulsed electrophoretic deposition - Miyazaki Hidetoshi; Yamane Mayoka; Mimaru Yu (Processing and Application of Ceramics, 2022)
Hydrophobic and hydrophilic coatings have been widely studied because of their functions such as anticorrosion and self-cleaning. In this study two different TiO2 suspensions, obtained by dispersing of hydrophilic and hydrophobic TiO2 particles in ethanol, were used for preparation of titania coatings on stainless steel substrates by pulsed electrophoretic deposition (EPD). The resultant hydrophilic and hydrophobic rytile TiO2 coatings showed random orientation and are dense with no cracks. The thicknesses of the coatings obtained using hydrophilic and hydrophobic TiO2 particles were 22.5 and 20.1 μm, respectively, whereas thier contact angles were 6.3° and 124.0°, respectively. The results show that hydrophilic and hydrophobic TiO2 coatings can be performed using pulsed EPD.